Clinical significance of bone marrow involvement by immunoglobulin gene rearrangement in de novo diffuse large B-cell lymphoma: a multicenter retrospective study - Kim, Yu Ri; Shin, Ho Jin; Yhim, Ho-Young; Yang, Deok-Hwan; Park, Yong; Lee, Ji Hyun; Lee, Won-Sik; Do, Young Rok; Mun, Yeung-Chul; Kim, Dae Sik; Kim, Jin Seok (Frontiers in Oncology, 2024)
Background: Bone marrow (BM) involvement is an indicator of a poor prognosis in diffuse large Bcell lymphoma (DLBCL); however, few studies have evaluated the role of immunoglobulin gene rearrangement (IgR) in detecting BM involvement.We evaluated the clinical characteristics and treatment outcomes of patients with DLBCL based on histological BM involvement or positive BM IgR using polymerase chain reaction or nextgeneration sequencing. We also investigated the role of consolidative upfront autologous hematopoietic stem cell transplantation (ASCT) in patients with DLBCL and BM involvement.Results: Among 624 patients, 123 (19.7%) with histological BM involvement and 88 (17.5%) with positive IgR in histologically negative BM had more advanced disease characteristics. Overall (OS) and progression-free (PFS) survival was better for patients with negative BM histology and negative IgR than that in patients with histological BM involvement (P = 0.050 and P < 0.001, respectively) and positive IgR with negative BM histology (P = 0.001 and P = 0.005, respectively). Survival rates did not differ among 82 (13.1%) patients who were treated with upfront ASCT and had histological BM involvement or positive IgR with negative BM histology. The survival outcomes were worse for patients who were not treated with upfront ASCT and for those with histological BM involvement or positive IgR, than for those with negative BM histology and negative IgR.Patients diagnosed with DLBCL and BM involvement based on histology or IgR had aggressive clinical features and poor survival. Upfront ASCT mitigated poor prognosis due to BM involvement.